1997
DOI: 10.3354/meps159001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dissolved organic nitrogen from rivers to estuarine eutrophication

Abstract: The bioavailibility of dissolved organic nitrogen (DON) in river water entering estuaries was examined for the Delaware and Hudson Rivers, USA. Water collected from above the salinity intrusion zone of each river was filtered, brought to a salinity of 15 ppt, and inoculated with estuarine bacteria. Bacterial production rates (8 to 26 X 105 cells ml-' d-') during the initial 2 d in these experiments were within the range measured in these and other estuaries, indicating that riverine dissolved organic matter ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(200 citation statements)
references
References 33 publications
(38 reference statements)
10
189
0
1
Order By: Relevance
“…The detrimental effects of nitrogen deposition on surface water chemistry have been widely reported both in Europe and North America (Evans and Monteith, 2001;Stoddard, 1994), however recent improvements caused by emission targets have occurred (Skjelkvale et al, 2005). While most studies have focussed on the effect of dissolved inorganic nitrogen (DIN) in terms of nitrogen cycling and water quality, the role of dissolved organic nitrogen (DON) in nitrogen cycling and bioavailability has also been shown to be important in a range of environments (Scott et al, 2007;Seitzinger et al, 2005;Jones et al, 2004;Willett et al, 2004;Seitzinger and Sanders, 1997;Carlsson and Graneli, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The detrimental effects of nitrogen deposition on surface water chemistry have been widely reported both in Europe and North America (Evans and Monteith, 2001;Stoddard, 1994), however recent improvements caused by emission targets have occurred (Skjelkvale et al, 2005). While most studies have focussed on the effect of dissolved inorganic nitrogen (DIN) in terms of nitrogen cycling and water quality, the role of dissolved organic nitrogen (DON) in nitrogen cycling and bioavailability has also been shown to be important in a range of environments (Scott et al, 2007;Seitzinger et al, 2005;Jones et al, 2004;Willett et al, 2004;Seitzinger and Sanders, 1997;Carlsson and Graneli, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…DIN is readily used by bacteria, algae, and higher plants. The biological availability of organic nitrogen inputs is less well documented, although a considerable portion is likely to be biologically labile [Seitzinger and Sanders, 1997]. In the current study, nitrous oxide production is estimated as a function of DIN inputs.…”
Section: Total Nitrogen (Tn) In Aquatic Systems Includes Dissolved Inmentioning
confidence: 99%
“…Most of the P leaves this lake in particulate form, and is prone to precipitation in the river plume on the shelf. Because organic and particulate N and P have different bioavailabilities to the primary and secondary producers than their inorganic counterparts (Seitzinger and Sanders 1997;Stepanauskas et al 1999), we also conclude that their input to the shelf may have severe impacts on coastal N and P cycling. A deficiency in inorganic relative to organic N may enhance the dominance of heterotrophic over autotrophic processes in coastal water, as was observed by Glibert et al (1991) in the Chesapeake Bay.…”
Section: Export Of N and P To The Black Seamentioning
confidence: 98%
“…An investigation on riverine nutrient transport to the Baltic Sea demonstrated that 52% of TN and 64% of TP occurred in the organic form (Stepanauskas et al 2002). Another study by Seitzinger and Sanders (1997) showed that in the Delaware and Hudson River (USA), organic N can account for 20-90% of the total riverine N load. In this study, we calculated the load of dissolved organic and particulate N and P to both lake complexes.…”
Section: Organic Matter and Particle Productionmentioning
confidence: 99%
See 1 more Smart Citation